PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI SDI PLUS AL ISHLAH TAMBAKREJO GURAH - Thoha Putra; Siti Qomariyah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
The right to get an education and to be able to develop is a right owned by every Indonesian. As a learning facilitator, the teacher has various roles. Teachers in achieving learning goals need to create an atmosphere of meaningful teaching and learning activities for students so that they can foster a desire to learn. Because when learning interest is lacking in learning activities it tends not to be wholeheartedly followed by students. The purpose of this research is to find out how the teacher's role is in increasing students' interest in learning mathematics in grade 2 SDI Plus Al Ishlah. This research was conducted using qualitative methods. The subjects of this study were math teachers in grade 2 at SDI Plus Al Ishlah, and were supported by the principal of SDI Plus Al Ishlah and grade 2 students at SDI Plus Al Ishlah. Data collection techniques using observation and interviews. The results of the data collected show that the teacher is able to carry out his role properly so that he can increase students' interest in learning mathematics. Efforts were made as follows: 1) Providing as much information as possible through various methods, 2) Providing feedback to students in the form of a stimulus, 3) Bringing students closer to teaching aids, 4) Involving students in activities related to mathematical material, and 5) The teacher guides students to learn from their own experiences.